Method for improving hardenability of gear steel bar and gear steel bar
By controlling superheat and electromagnetic stirring, and transforming equiaxed to columnar crystals through rolling, the method addresses uneven solute distribution in gear steel bars, enhancing hardenability and mechanical properties.
Patent Information
- Application Number
- CN202411304681.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-19
AI Technical Summary
The hardenability of gear steel bars fluctuates significantly due to uneven solute distribution and anisotropy during the heat treatment process, leading to increased distortion and reduced service performance.
A method involving controlled superheat, electromagnetic stirring, and rolling processes to transform the equiaxed crystal area to columnar crystals, ensuring uniform solute distribution and reducing the difference between A and B surfaces of J9 and J15 to ≤1.5HRC.
Significantly reduces solute fluctuation and hardenability differences, achieving uniform solute distribution and improved mechanical properties in gear steel bars, meeting high-end automotive requirements.
Smart Images

Figure CN119187485A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of continuous casting technology, and in particular relates to a method for improving the hardenability of a gear steel bar and the gear steel bar. Background Art
[0002] As a key part of the transmission mechanism of automobile gearbox, gears need to withstand impact, bending and contact stress during operation, and are required to have good toughness and wear resistance. Carburizing and quenching are common means for gears to achieve surface hardness and core toughness. Usually, when the hardenability of gear steel fluctuates greatly, uneven distortion will occur during the heat treatment process, which will directly deteriorate the service performance and service life of the gear. Therefore, current high-end automotive users require that the hardenability bandwidth of the same furnace of steel is ≤4HRC, and that the difference between the A and B sides of each bar hardenability J9 and J15 is ≤2HRC.
[0003] The hardenability of steel is closely related to the uniformity of matrix solute distribution. The more uniform the solute distribution, the smaller the hardenability fluctuation. Usually, during the solidification process of the ingot, solute redistribution and selective crystallization will occur. The cast matrix must have uneven composition. Considering the influence of solidification structure morphology and size on solute distribution, the matrix composition unevenness can reach semi-macroscopic or macroscopic scale, which cannot be completely removed by rolling and heat treatment. It is inherited to the gear, resulting in increased hardenability fluctuation and anisotropy of heat treatment deformation. In addition, controlling the number of passes in the rolling process and the cross-sectional compression ratio of each pass is crucial to the hardenability of steel. If the interface compression ratio of each pass cannot be accurately controlled, it may lead to uneven grain refinement and uneven solute distribution, which in turn affects the hardenability of gear steel. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a method for improving the hardenability of gear steel bars and gear steel bars. By controlling the superheat, electromagnetic stirring of the crystallizer, the pressing process and the rolling process, the equiaxed crystal area of the ingot and the bar is reduced, and the formation of semi-macroscopic point segregation in the equiaxed crystal area is suppressed. The cast structure in the hardenability detection area of the bar is transformed from equiaxed crystals to columnar crystals, and the cross-sectional solute extreme and standard deviation and the uniformity of the solute distribution of the dendrite structure are further improved. The difference between the A and B surfaces of J9 and J15 is ≤1.5HRC, and the hardenability index is qualified, which is conducive to reducing the uneven distortion of subsequent gear heat treatment and improving the homogeneity of the product.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] On the one hand, the present invention provides a method for improving the hardenability of gear steel bars, wherein the difference between the A and B surfaces of J9 and J15 of the gear steel is not greater than 1.5HRC, and the method is characterized in that it comprises: casting molten steel with qualified composition through a continuous casting machine; adopting a reduction process in the solidification stage; after solidification, rolling the hot ingot; during the continuous casting process, the superheat of the tundish is 40-45°C, and the electromagnetic stirring current of the crystallizer is 50-150A; the reduction amount is controlled by the change of the solid phase ratio at the center of the ingot, the solid phase ratio at the center of the reduction area is 0.05-1.0, and the reduction amount in the continuous casting reduction area corresponding to the central solid phase ratio being less than 0.3 is not less than 1mm and not more than 3mm; the rolling section compression ratio is not less than 90%.
[0007] Furthermore, the casting process parameters are: constant temperature and constant pulling speed during the continuous casting process, the pulling speed is 0.95-1.15m / min, the secondary cooling water volume is 0.33-0.35L / kg, and the electromagnetic stirring current at the end of solidification is 100-200A.
[0008] Furthermore, the maximum single pressing amount satisfies the following formula:
[0009]
[0010] Among them, ε is the maximum critical strain, v is the working pulling speed, h is the thickness of the ingot, r is the diameter of the reduction roll, b is the roll spacing, and a is the maximum single reduction.
[0011] Furthermore, when the solid fraction at the center of the compression area is within 0.05-1.0, the total compression amount is calculated as follows:
[0012]
[0013] in, is the reduction coefficient, which ranges from 0.8 to 1.1, A is the total amount of reduction, V R is the pressing rate, t is the time, h is the thickness of the billet, W is the width of the billet, T L is the liquidus temperature of the steel grade, T S is the solidus temperature of the steel grade.
[0014] Furthermore, the relationship between the reduction amount and the central solid phase ratio is:
[0015] When 0.05≤f s ≤0.08, the pressing amount is 1mm; when 0.18≤f s ≤0.20, the pressing amount is 2mm; when 0.55≤f s ≤0.58, the pressing amount is 2mm; when 0.98≤f s ≤1, the pressing amount is 2mm.
[0016] Furthermore, the steel used for rolling the bar is 20CrMnTiH steel.
[0017] Furthermore, the rolling process is as follows: heating the hot ingot to a temperature of 1160-1200°C and keeping it warm for 150 minutes, starting rolling at a temperature of 1060-1100°C, finishing rolling at a temperature of 900-1000°C, rolling it into a φ70mm bar, and then cooling it to obtain the bar.
[0018] Furthermore, 4 to 6 rolling passes are adopted, the cross-sectional compression ratio of the first rolling pass is not less than 50%, the cross-sectional compression ratio of the last rolling pass is 10% to 25%, and the cross-sectional compression ratio of each of the remaining rolling passes is 30% to 45%.
[0019] Furthermore, the continuous casting machine is a full-arc continuous casting machine with six machines and six streams, and a casting section of 200mm×240mm.
[0020] A gear steel bar is prepared by the above method.
[0021] The beneficial effects brought by the technical solution provided by the embodiment of the present invention include:
[0022] (1) The present invention adjusts the continuous casting process parameters, that is, increases the superheat, reduces the electromagnetic stirring of the crystallizer and implements light pressure at the end of solidification, and combines the subsequent rolling process to significantly reduce the equiaxed crystal area of the prepared continuous casting billet, and make the solute distribution of the cross section of the casting billet more uniform. The cross-sectional solute C extreme difference and standard deviation of the continuous casting billet prepared by the continuous casting process parameter method of the present invention are reduced from 0.02wt.% and 0.007wt.% to 0.01wt.% and 0.003wt.%, respectively; the cross-sectional Cr extreme difference and standard deviation are reduced from 0.09wt.% and 0.022wt.% to 0.05wt.% and 0.016wt.%, respectively, and the cross-sectional Mn extreme difference and standard deviation are reduced from 0.08wt.% and 0.020wt.% to 0.03wt.% and 0.010wt.%, respectively, and the solute fluctuation is significantly reduced. The range and standard deviation of C in the cross section of the prepared rod were reduced from 0.02wt.% and 0.005wt.% to 0.01wt.% and 0.002wt.%, respectively, the range and standard deviation of Cr in the cross section were reduced from 0.04wt.% and 0.013wt.% to 0.03wt.% and 0.009wt.%, respectively, and the range and standard deviation of Mn in the cross section were reduced from 0.04wt.% and 0.012wt.% to 0.01wt.% and 0.005wt.%, respectively. The solute distribution of the rod was more uniform; the as-cast structure in the hardenability detection area of the rod was transformed from equiaxed crystal to columnar crystal zone, and the average contents of solute C, Cr and Mn in the dendrite structure were reduced from 0.42wt.%, 1.95wt.% and 1.31wt.% to 0.41wt.%, 1.92wt.%, respectively. t.%, 1.27wt.%; the maximum segregation ratios of C, Cr and Mn solutes are reduced from 2.75, 2.24 and 3.73 to 2.41, 2.16 and 3.30 respectively; the differences between the three hardenability test results J9-A and J9-B of the prepared bars are reduced from 2.3HRC, 3.0HRC and 2.7HRC to 0.6HRC, 0.7HRC and 0.2HRC respectively; the differences between J15-A and J15-B are reduced from 4.1HRC, 2.5HRC and 3.2HRC to 0.3HRC, 1.5HRC and 1.3HRC respectively; the fluctuations in the hardenability of the A and B surfaces are significantly reduced, both of which are less than the 2HRC required by the index, and the bars prepared by the technical scheme of the present application have excellent performance and obvious fluctuation reduction effect, which does not exceed 1.5HRC.
[0023] (2) In the continuous casting process of the present invention, the superheat is increased and the current of the electromagnetic stirring of the crystallizer is reduced, so that the equiaxed crystal rate of the ingot is reduced from 26.42% to 6.69%, and the equiaxed crystal rate of the rod is reduced from 24.89% to 4.09%; on this basis, the pressing roller is pressed down by 7mm in the range of the central solid phase fraction of 0.05-1.00, the convective heat transfer is enhanced, the local cooling rate increases sharply, the existing crystal nuclei solidify rapidly, and the dendrites cannot bridge each other, thereby reducing or even eliminating the aggregation of concentrated molten steel in the center under the action of negative pressure suction during solidification, and the final organization is fine equiaxed crystals, and the point segregation is small in size and small in number, so that the as-cast organization in the hardenability detection area of the rod is transformed from equiaxed crystals to columnar crystals, and the solute is evenly distributed, which is beneficial to improving the consistency of the A and B surfaces in the terminal quenching experiment. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 A schematic diagram of sampling a casting slab prepared in an embodiment of the present invention;
[0026] Figure 2 Schematic diagram of sampling of the rod prepared in the embodiment of the present invention, a is the solute content detection position; b is the sampling position of the sample dendrite morphology, c is the sampling position of the rod hardenability detection, and d is the J9 and J15 positions;
[0027] Figure 3 This is a low-magnification metallographic image of a cross section of a casting slab prepared in Example 1 of the present invention;
[0028] Figure 4 The solute content distribution at different positions of the ingot prepared in Example 1 of the present invention;
[0029] Figure 5 The solute content distribution at different positions of the rod prepared in Example 1 of the present invention;
[0030] Figure 6 This is an EPMA scanning result diagram of the hardenability test area of the bar prepared in Example 1 of the present invention;
[0031] Figure 7 These are the A and B surface test results of the hardenability J9 and J15 of the bars prepared in Example 1 of the present invention.
[0032] Figure 8 Low magnification metallographic image of the cross section of the ingot prepared in Comparative Example 1 of the present invention
[0033] Fig. 9 The solute content distribution at different positions of the ingot prepared in Comparative Example 1 of the present invention;
[0034] Fig.10 The solute content distribution at different positions of the rod prepared in Comparative Example 1 of the present invention;
[0035] Fig.11 This is an EPMA scanning result diagram of the hardenability test area of the bar prepared in Comparative Example 1 of the present invention;
[0036] Fig.12 The A and B surface test results of the hardenability J9 and J15 of the bars prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0038] An embodiment of the present invention provides a method for improving the hardenability of gear steel bars, wherein the difference between the A and B surfaces of J9 and J15 of the gear steel is not greater than 1.5HRC, comprising: casting molten steel with qualified composition through a continuous casting machine; adopting a reduction process in the solidification stage; after solidification, rolling the hot ingot; during the continuous casting process, the superheat of the tundish is 40-45°C, and the electromagnetic stirring current of the crystallizer is 50-150A; the reduction process controls the reduction amount by changing the solid phase ratio at the center of the ingot, the solid phase ratio at the center of the reduction area is 0.05-1.0, and in the continuous casting reduction area corresponding to the central solid phase ratio being less than 0.3, the reduction amount is not less than 1mm and not more than 3mm; the rolled section compression ratio is not less than 90%.
[0039] The present invention adjusts the continuous casting process parameters, i.e., increases the superheat, reduces the electromagnetic stirring of the crystallizer and implements light reduction at the end of solidification at the same time, and combines with the subsequent rolling process, so that the equiaxed crystal area of the prepared continuous casting billet is significantly reduced, and the solute distribution of the cross section of the casting billet is more uniform. The cross section solute C extreme difference and standard deviation of the continuous casting billet prepared by the continuous casting process parameter method of the present invention are respectively reduced from 0.02wt.% and 0.007wt.% to 0.01wt.% and 0.003wt.%, the cross section Cr extreme difference and standard deviation are respectively reduced from 0.09wt.% and 0.022wt.% to 0.05wt.% and 0.016wt.%, and the cross section Mn extreme difference and standard deviation are respectively reduced from 0.08wt.% and 0.020wt.% to 0.03wt.% and 0.010wt.%, and the solute fluctuation is significantly reduced. The range and standard deviation of C in the cross section of the prepared rod were reduced from 0.02wt.% and 0.005wt.% to 0.01wt.% and 0.002wt.%, respectively, the range and standard deviation of Cr in the cross section were reduced from 0.04wt.% and 0.013wt.% to 0.03wt.% and 0.009wt.%, respectively, and the range and standard deviation of Mn in the cross section were reduced from 0.04wt.% and 0.012wt.% to 0.01wt.% and 0.005wt.%, respectively. The solute distribution of the rod was more uniform; the as-cast structure in the hardenability detection area of the rod was transformed from equiaxed crystal to columnar crystal zone, and the average contents of solute C, Cr and Mn in the dendrite structure were reduced from 0.42wt.%, 1.95wt.% and 1.31wt.% to 0.41wt.%, 1.92wt.%, respectively. t.%, 1.27wt.%; the maximum segregation ratios of C, Cr and Mn solutes are reduced from 2.75, 2.24 and 3.73 to 2.41, 2.16 and 3.30 respectively; the differences between the three hardenability test results J9-A and J9-B of the prepared bars are reduced from 2.3HRC, 3.0HRC and 2.7HRC to 0.6HRC, 0.7HRC and 0.2HRC respectively; the differences between J15-A and J15-B are reduced from 4.1HRC, 2.5HRC and 3.2HRC to 0.3HRC, 1.5HRC and 1.3HRC respectively; the fluctuations in the hardenability of the A and B surfaces are significantly reduced, both of which are less than the 2HRC required by the index, and the bars prepared by the technical scheme of the present application have excellent performance and obvious fluctuation reduction effect, which does not exceed 1.5HRC.
[0040] The technical solution proposed in the present invention is used to prepare a medium-carbon low-alloy steel ingot that meets the requirement that the difference between the A and B surfaces of J9 and J15 is less than 2HRC, while the difference between the A and B surfaces of J9 and J15 in the prior art is usually much greater than 2HRC. For example, it is believed in the prior art that the flatness of the solidification interface of equiaxed crystals is worse than that of columnar crystals, which is more conducive to the formation of large-area point segregation, resulting in great fluctuations in the solute distribution of the ingot section, and the solute uniformity distribution is significantly related to the fluctuation of hardenability. The present invention is based on a continuous casting process (high superheat, weak crystallizer electromagnetic stirring, implementation of light pressure at the end of solidification and combined with subsequent rolling process) based on solidification structure regulation to reduce the equiaxed crystal area of the ingot and then improve the point segregation, and improve the uniformity of solute distribution in the ingot and bar sections.
[0041] The molten steel with qualified composition after BOF+LF+VD refining is cast through a continuous casting machine. The continuous casting process is constant temperature and constant pulling speed, the pulling speed is 0.95-1.15m / min, the secondary cooling water volume is 0.33-0.35L / kg, and the electromagnetic stirring at the end of solidification is 100-200A. In the existing continuous casting process, keeping the molten steel low in superheat pouring and strong crystallizer electromagnetic stirring can increase the equiaxed crystal rate of the ingot, thereby reducing the problems of central shrinkage and central segregation caused by overdeveloped columnar crystals. However, for the regulation of semi-macro segregation, inhibiting the development of equiaxed crystals is more effective in reducing the size of point segregation and solute concentration in the ingot. The flatness of the solidification interface of equiaxed crystals is worse than that of columnar crystals, which is more conducive to the formation of large-area point segregation. The casting process in the continuous casting process proposed by the present invention, through the combination of the above-mentioned process parameters with the pressure control method and the rolling process, finally realizes the technical indicators proposed by the present invention, so that the prepared continuous casting ingot can be further processed after being rolled into bars to prepare gear steel bars that meet the index requirements.
[0042] In order to ensure that cracks do not appear in the ingot during the pressing process, the molten steel flows quickly, the convective heat transfer is enhanced, the local cooling rate increases sharply, the existing crystal nuclei solidify quickly, and the dendrites cannot bridge each other, the maximum single pressing amount is limited. Specifically, the maximum single pressing amount satisfies the following formula:
[0043]
[0044] Among them, ε is the maximum critical strain, and the embodiment of the present invention adopts 20CrMnTiH steel, and the value is 0.71%, v is the working pulling speed, h is the thickness of the ingot, r is the diameter of the reduction roll, b is the roll spacing, and a is the single maximum reduction amount.
[0045] In the embodiment of the present invention, v = 0.95-1.15 m / min; h = 200 mm; r = 350 mm; b = 855 mm. Through calculation, the maximum single pressing amount a is not greater than 2 mm.
[0046] When the solid fraction at the center of the reduction zone is between 0.05 and 1.0, the total reduction is calculated as follows:
[0047]
[0048] in, is the reduction coefficient, which ranges from 0.8 to 1.1, A is the total amount of reduction, V R is the pressing rate, t is the time, h is the thickness of the billet, W is the width of the billet, T L is the liquidus temperature of the steel grade, T S is the solidus temperature of the steel grade.
[0049] The maximum single reduction and the total reduction of the present invention comprehensively consider the geometric dimensions of the rollers and the composition content of the 20CrMnTiH steel proposed in the present invention, and prepare a continuous casting billet that meets the corresponding technical indicators.
[0050] In order to suppress both macroscopic and semi-macroscopic segregation, when 0.05≤f s ≤0.08, the pressing amount is 1mm; when 0.18≤f s ≤0.20, the pressing amount is 2mm; when 0.55≤f s ≤0.58, the pressing amount is 2mm; when 0.98≤f s ≤1, the reduction is 2mm. The reduction roller is pressed down by 7mm in the range of 0.05-1.00 in the center solid phase ratio, the convective heat transfer is enhanced, the local cooling rate increases sharply, the existing nuclei solidify rapidly, the dendrites cannot bridge, thus reducing or even eliminating the aggregation of concentrated molten steel in the center under the action of negative pressure suction of solidification, and the final organization is fine equiaxed crystals, the point segregation is small in size and small in number, so that the as-cast organization in the hardenability test area of the bar is transformed from equiaxed crystals to columnar crystals, and the solute is evenly distributed, which is conducive to improving the consistency of A and B surfaces in the end quenching experiment.
[0051] The gear steel used in the embodiment of the present invention is 20CrMnTiH steel, and the specific composition is shown in Table 1.
[0052] Table 1 Chemical composition of 20CrMnTiH steel (wt%)
[0053] serial number C Mn Si P S Cr Ti Standard range 0.17-0.23 0.80-1.20 0.17-0.37 ≤0.030 ≤0.030 1.00-1.20 0.04-0.10
[0054] The embodiment of the present invention is produced by a full-arc continuous casting machine, with six machines and six streams, and a casting section of 200mm×240mm.
[0055] The rolling process is as follows: the hot ingot is heated to 1160-1200℃ and kept warm for 150min, the start rolling temperature is 1060-1100℃, the final rolling temperature is 900-1000℃, and the ingot is rolled into a φ70mm bar, and then cooled to obtain the bar. Specifically, the rolling process is as follows: the ingot is sent hot to the rolling mill after it comes off the line, the heating section temperature is 1160℃, the soaking section temperature is 1200℃, the heating and holding time is 150min, the start rolling temperature is 1060-1100℃, the final rolling temperature is 900-1000℃, and the rolling specifications are After rolling, it is sent to a slow cooling pit for slow cooling, with a cooling rate of less than 0.63℃ / s.
[0056] Specifically, in order to improve the refinement of bar grains and the uniformity of solute distribution during the rolling process, thereby improving the hardenability of steel, the present invention implements 4 to 6 rolling passes in the rolling process, and according to the cross-sectional compression ratio of each pass, the rolling process is carefully divided into three stages: rough rolling, intermediate rolling and finishing rolling. In the rough rolling stage, that is, the first rolling pass, the cross-sectional compression ratio is ensured to be no less than 50%. Through large-scale deformation, the cast defects are effectively eliminated, laying the foundation for the uniformity of the organization, and promoting the initial refinement of the grains, while promoting the initial uniform distribution of the solute elements. In the finishing stage, that is, the last rolling pass, the cross-sectional compression ratio is controlled at 10% to 25%. Through precise small deformation, the extreme refinement of the grains is achieved, the solute distribution is more uniform, and the surface quality of the bar is improved. The intermediate rolling stage covers the remaining rolling passes, and the cross-sectional compression ratio of each pass is between 30% and 45%. This stage further refines the grains, reduces segregation, provides conditions for the uniform distribution of solute elements, improves the internal structure, enhances the strength and toughness of the material, and ultimately ensures that the rod has excellent mechanical properties and hardenability.
[0057] An embodiment of the present invention further provides a gear steel bar, which is prepared by the above method.
[0058] Characterization of the prepared products:
[0059] 1) In order to measure the solute content fluctuation of the cross section of the continuous casting billet and bar, the sampling method for the continuous casting billet is as follows: Figure 1 As shown in the figure, the inner arc side is the inner side of the ingot produced by the full arc continuous casting machine, and the outer arc side is the outer side of the ingot produced by the full arc continuous casting machine. Sampling and testing are carried out on the inner and outer arc sides and the horizontal side of the ingot cross section respectively; the sampling method for bars is as follows Figure 2 As shown in a, three surfaces are selected for measurement. In order to make the detection result more accurate, the distance between two adjacent surfaces is 20-30 mm.
[0060] 2) In order to explore the dendrite morphology in the hardenability area of the bar, the sampling position of the dendrite morphology of the transverse sample of the bar is as follows: Figure 2 As shown in b, sample C with a cross section of 10mm×10mm×10mm is taken at a distance of 15mm from the surface in the radial direction. The dendritic structure corrosion method of this study is: the sample is heated to 930℃ at 10℃ / min and kept warm for 0.5h, then cooled to 680℃ at 5℃ / min and kept warm for 1h, and then furnace cooled to room temperature; the sample is processed to the mirror level by a metallographic grinder and etched with 4% nitric acid alcohol for 20-30s, and the dendritic morphology can be observed. The C, Cr, and Mn solute distribution of the dendritic structure of sample C was scanned by an electron probe (EPMA1720, Shimadzu, Japan), and the scanning area was 3.00mm×2.25mm, as shown in FIG. Figure 2 As shown in the green rectangular area in b, the uppermost side of the scanning position of sample C is 15 mm from the center; the scanning step length is 10 μm, and the EPMA surface scan includes the hardenability detection area.
[0061] 3) In order to explore the influence of different solidification structures on the hardenability of bars, the hardenability test of 20CrMnTiH bars was carried out. The hardenability test standard of gear steel 20CrMnTiH mainly implements GB / T 225-2006. Before preparing the hardenability sample, the φ70mm round steel needs to be pre-heat treated. The heat treatment system is 930℃ for 1h and then air cooled to room temperature. The hardenability test standard implements GB / T 225-2006. The experimental sampling position is as follows: Figure 2 As shown in the red area c, 3 samples were taken from the embodiment and comparative example bars respectively, and the axis angle of each sample was 120°. The size of the obtained sample was φ25mm×100mm. Then, the sample was subjected to end quenching test. After the A and B surfaces of the quenched sample were ground by 0.5mm respectively, the hardness was measured at 9mm and 15mm away from the end quenching surface. Figure 2 As shown in d, the obtained data are the hardness values of the A and B surfaces of J9 and J15.
[0062] In order to better illustrate the embodiments of the present invention, the present invention is further described in detail below through specific examples.
[0063] Example 1
[0064] The present embodiment provides a method for improving the hardenability of gear steel bars, and a method for preparing gear steel bars using the method, wherein the steel for the bars is 20CrMnTiH, and qualified molten steel refined by BOF+LF+VD is cast, using a six-machine six-stream full-arc continuous casting machine, with a casting section of 200mm×240mm, a tundish superheat of 40°C, a crystallizer electromagnetic stirring current of 100A, a pulling speed of 1.05m / min, a secondary cooling water volume of 0.33L / kg, and a terminal electromagnetic stirring current of 150A.
[0065] The solid fraction at the center fs = 0.05, press down 1mm, at the center solid fraction f s = 0.20, press down 2mm, at the center solid fraction f s = 0.57, press down 2mm, at the center solid fraction f s =1.00 and press down 2mm, and take samples of the cooled ingot for analysis.
[0066] After solidification, the hot ingot was heated to 1160℃ and kept at this temperature for 150min. The starting rolling temperature was 1060℃ and the final rolling temperature was 950℃. The bar is then cooled to obtain the bar, specifically, four rolling passes are used, the cross-sectional compression ratio of one rolling pass is 64%, the cross-sectional compression ratio of the last rolling pass is 25%, and the cross-sectional compression ratio of each of the remaining rolling passes is 45%. The bar is sampled and analyzed.
[0067] like Figure 3 As shown, the equiaxed crystal ratio of the ingot prepared in this embodiment is 6.69%, and the center quality is generally good.
[0068] like Figure 4 As shown, it can be seen that the range and standard deviation of solute C in the cross section of the ingot prepared in this embodiment are 0.01wt.% and 0.003wt.%, respectively; the range and standard deviation of Cr in the cross section are 0.05wt.% and 0.016wt.%, respectively; and the range and standard deviation of Mn in the cross section are 0.03wt.% and 0.010wt.%, respectively.
[0069] like Figure 5 As shown, it can be seen that the range and standard deviation of solute C in the cross section of the rod prepared in this embodiment are 0.01wt.% and 0.002wt.%, the range and standard deviation of Cr in the cross section are 0.03wt.% and 0.009wt.%, and the range and standard deviation of Mn in the cross section are 0.01wt.% and 0.005wt.%.
[0070] like Figure 6 As shown, the hardenability test area of the prepared rod is columnar crystal, and the average contents of solute C, Cr and Mn are 0.41wt.%, 1.92wt.%, and 1.27wt.%, respectively; the maximum segregation ratios of C, Cr, and Mn solutes are 2.41, 2.16, and 3.30, respectively.
[0071] Figure 7The test results of the A and B surfaces of the three hardenability test samples J9 and J15 are shown. It can be seen that the differences between the A and B surfaces of the three hardenability indicators J9 are 0.6HRC, 0.7HRC and 0.2HRC respectively, and the differences between the A and B surfaces of J15 are 0.3HRC, 1.5HRC and 1.3HRC respectively. The fluctuation of the hardenability of the A and B surfaces is significantly reduced, and both are less than the required 2HRC.
[0072] Example 2
[0073] The present embodiment provides a method for improving the hardenability of gear steel bars, and a method for preparing gear steel bars using the method. The steel for the bars is 20CrMnTiH. Qualified molten steel refined by BOF+LF+VD is cast. A six-machine, six-stream full-arc continuous casting machine is used. The casting section is 200mm×240mm, the superheat of the tundish is 40°C, the electromagnetic stirring current of the crystallizer is 50A, the pulling speed is 0.95m / min, the secondary cooling water volume is 0.33L / kg, and the terminal electromagnetic stirring current is 100A.
[0074] The solid fraction at the center f s = 0.05, press down 1mm, at the center solid fraction f s = 0.18, press down 2mm, at the center solid fraction f s = 0.55, press down 2mm, at the center solid fraction f s =0.98 and press down 2mm, and take samples of the cooled ingot for analysis.
[0075] After solidification, the hot ingot was heated to 1160℃ and kept at this temperature for 150min. The starting rolling temperature was 1060℃ and the final rolling temperature was 900℃. The bar is then cooled to obtain the bar, specifically, five rolling passes are adopted, the cross-sectional compression ratio of one rolling pass is 50%, the cross-sectional compression ratio of the last rolling pass is 10%, and the cross-sectional compression ratio of each of the remaining rolling passes is 30-45%. The bar is sampled and analyzed.
[0076] The equiaxed crystal ratio of the ingot prepared in this embodiment is 7.0%, the cross section has no central shrinkage cavity, the range and standard deviation of solute C in the cross section of the ingot are 0.02wt.% and 0.004wt.%, the range and standard deviation of Cr in the cross section are 0.06wt.% and 0.018wt.%, and the range and standard deviation of Mn in the cross section are 0.05wt.% and 0.014wt.%.
[0077] The range and standard deviation of solute C in the cross section of the rod prepared in this embodiment are 0.02wt.% and 0.002wt.%, respectively; the range and standard deviation of Cr in the cross section are 0.03wt.% and 0.010wt.%, respectively; and the range and standard deviation of Mn in the cross section are 0.02wt.% and 0.006wt.%, respectively.
[0078] The average contents of solute C, Cr and Mn in the dendrite structure of the rod prepared in this embodiment in the hardenability test area are 0.41wt.%, 1.93wt.% and 1.28wt.%, respectively; the maximum segregation ratios of C, Cr and Mn solutes are 2.46, 2.18 and 3.38, respectively.
[0079] The A and B surface test results of the three hardenability tests of the rolled material samples J9 and J15 prepared in this embodiment show that the differences between the A and B surfaces of J9 are 0.9HRC, 1.2HRC and 0.9HRC respectively, and the differences between the A and B surfaces of J15 are 0.8HRC, 1.3HRC and 1.1HRC respectively.
[0080] Example 3
[0081] The present embodiment provides a method for improving the hardenability of gear steel bars, and a method for preparing gear steel bars using the method. The steel for the bars is 20CrMnTiH. Qualified molten steel refined by BOF+LF+VD is cast. A six-machine, six-stream full-arc continuous casting machine is used. The casting section is 200mm×240mm, the superheat of the tundish is 45°C, the electromagnetic stirring current of the crystallizer is 150A, the pulling speed is 1.15m / min, the secondary cooling water volume is 0.35L / kg, and the terminal electromagnetic stirring current is 200A.
[0082] The solid fraction at the center f s = 0.08, press down 1mm, at the center solid fraction f s = 0.20, press down 2mm, at the center solid fraction f s = 0.58, press down 2mm, at the center solid phase ratio f s =1, press down 2mm, and take samples of the cooled ingot for analysis.
[0083] After solidification, the hot ingot is heated to 1200℃ and kept at this temperature for 150min. The starting rolling temperature is 1100℃ and the final rolling temperature is 1000℃. The bar is then cooled to obtain the bar, specifically, six rolling passes are used, the cross-sectional compression ratio of one rolling pass is 50%, the cross-sectional compression ratio of the last rolling pass is 10%, and the cross-sectional compression ratio of each of the remaining rolling passes is 30-45%. The bar is sampled and analyzed.
[0084] The equiaxed crystal ratio of the ingot prepared in this embodiment is 7.2%, the cross section has no central shrinkage cavity, the range and standard deviation of solute C in the cross section of the ingot are 0.02wt.% and 0.005wt.%, the range and standard deviation of Cr in the cross section are 0.07wt.% and 0.0170wt.%, and the range and standard deviation of Mn in the cross section are 0.06wt.% and 0.014wt.%.
[0085] The range and standard deviation of solute C in the cross section of the rod prepared in this embodiment are 0.02wt.% and 0.004wt.%, respectively; the range and standard deviation of Cr in the cross section are 0.03wt.% and 0.011wt.%, respectively; and the range and standard deviation of Mn in the cross section are 0.02wt.% and 0.008wt.%, respectively.
[0086] The average contents of solute C, Cr and Mn in the dendrite structure of the rod prepared in this embodiment in the hardenability test area are 0.41wt.%, 1.93wt.% and 1.29wt.%, respectively; the maximum segregation ratios of C, Cr and Mn solutes are 2.50, 2.19 and 3.42, respectively.
[0087] The A and B surface test results of the three hardenability tests of the rolled material samples J9 and J15 prepared in this embodiment show that the differences between the A and B surfaces of J9 are 1.0HRC, 1.3HRC and 1.1HRC respectively, and the differences between the A and B surfaces of J15 are 0.9HRC, 1.4HRC and 1.2HRC respectively.
[0088] Comparative Example 1
[0089] Different from Example 1, in Comparative Example 1, the superheat is 35° C., the electromagnetic stirring of the crystallizer is 300 A, and pressure reduction control is not adopted, that is, pressure reduction operation is not adopted in the range of the central solid phase ratio of 0-1.
[0090] like Figure 8 As shown, the equiaxed crystal rate of the ingot prepared in this comparative example is 26.42%. Compared with the columnar crystal area, the interdendritic segregation in the equiaxed crystal area is more obvious, and the dark spots formed by solute aggregation are large in size and large in number, which is a typical point segregation.
[0091] like Fig. 9 As shown, the range and standard deviation of the cross-section solute C of the ingot prepared in this comparative example are 0.02wt.% and 0.007wt.%, the range and standard deviation of the cross-section Cr are 0.09wt.% and 0.022wt.%, and the range and standard deviation of the cross-section Mn are 0.08wt.% and 0.020wt.%. Compared with Example 1, the cross-section solute distribution of the ingot fluctuates significantly.
[0092] like Fig.10As shown, the range and standard deviation of the cross-section solute C of the rod prepared in this comparative example are 0.02wt.% and 0.005wt.%, the range and standard deviation of the cross-section Cr are 0.04wt.% and 0.013wt.%, and the range and standard deviation of the cross-section Mn are 0.04wt.% and 0.012wt.%. Compared with the examples, the solute C, Cr and Mn of the comparative example fluctuate significantly.
[0093] like Fig.11 As shown, the hardenability test area of the rod prepared in this comparative example is a typical equiaxed crystal area, and the average contents of dendrite tissue solutes C, Cr and Mn are 0.42wt.%, 1.95wt.%, and 1.31wt.%, respectively; the maximum segregation ratios of C, Cr, and Mn solutes are 2.75, 2.24, and 3.73, respectively. Compared with the embodiment, the dendrite tissue solutes C, Cr, and Mn of the comparative example are significantly enriched.
[0094] like Fig.12 As shown in the figure, the A and B surface test results of the three hardenability tests of the bar samples J9 and J15 prepared in this comparative example, the difference between the A and B surfaces of J9 is 2.3HRC, 3.0HRC and 2.7HRC respectively, and the difference between the A and B surfaces of J15 is 4.1HRC, 2.5HRC and 3.2HRC respectively. The difference between the A and B surfaces of the comparative example bar hardenability J9 and J15 is much greater than 2HRC.
[0095] Comparative Example 2
[0096] Different from Example 1, the superheat degree in this comparative example is 35°C.
[0097] The A and B surface test results of the three hardenability tests of the bar samples J9 and J15 prepared in this comparative example showed that the differences between the A and B surfaces of J9 were 2.1HRC, 2.5HRC and 2.4HRC respectively, and the differences between the A and B surfaces of J15 were 2.0HRC, 2.6HRC and 2.3HRC respectively.
[0098] Comparative Example 3
[0099] Different from Example 1, the electromagnetic stirring of the crystallizer in this comparative example is 300A.
[0100] The A and B surface test results of the three hardenability tests of the bar samples J9 and J15 prepared in this comparative example showed that the differences between the A and B surfaces of J9 were 1.9HRC, 2.4HRC and 2.1HRC respectively, and the differences between the A and B surfaces of J15 were 2.3HRC, 2.8HRC and 2.2HRC respectively.
[0101] Comparative Example 4
[0102] Different from Example 1, this comparative example does not use pressure reduction control, that is, no pressure reduction operation is used in the range of the central solid phase ratio of 0-1.
[0103] The A and B surface test results of the three hardenability tests of the bar samples J9 and J15 prepared in this comparative example showed that the differences between the A and B surfaces of J9 were 2.3HRC, 2.9HRC and 2.4HRC respectively, and the differences between the A and B surfaces of J15 were 3.8HRC, 2.8HRC and 3.3HRC respectively.
[0104] Comparative Example 5
[0105] Different from Example 1, the rolling process in this comparative example is: 5 rolling passes, the cross-sectional compression ratio of the first rolling pass is 45%, the cross-sectional compression ratio of the last rolling pass is 30%, and the cross-sectional compression ratio of each of the remaining rolling passes is 30% to 45%.
[0106] The A and B surface test results of the three hardenability tests of the bar samples J9 and J15 prepared in this comparative example showed that the differences between the A and B surfaces of J9 were 1.8HRC, 1.7HRC and 2.1HRC respectively, and the differences between the A and B surfaces of J15 were 1.9HRC, 2.2HRC and 1.8HRC respectively.
[0107] It can be seen from Example 1 and Comparative Examples 1-5 that the solute C, Cr and Mn in the cross-section of the ingot prepared by the technical solution provided by the present invention are evenly distributed, the equiaxed crystal area of the ingot is reduced, the number of point segregations is small and the size is small; the dendrite structure in the hardenability test area of the bar is columnar crystal, and the solute is evenly distributed; the technical agreement indicators of downstream customers are met.
[0108] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for improving the hardenability of gear steel bars, wherein the difference between the A and B surfaces of J9 and J15 of the gear steel is not greater than 1.5HRC, characterized in that: include: The molten steel with qualified composition is cast through a continuous casting machine; During the solidification stage, a press-down process is used; After solidification, the hot ingot is rolled; During the continuous casting process, the overheat degree of the tundish is 40-45°C, and the electromagnetic stirring current of the crystallizer is 50-150A; the reduction process is to control the reduction amount by changing the solid phase ratio at the center of the ingot, the solid phase ratio at the center of the reduction area is 0.05-1.0, and in the continuous casting reduction area corresponding to the central solid phase ratio being less than 0.3, the reduction amount is not less than 1mm and not more than 3mm; the rolled section compression ratio is not less than 90%.
2. The method for improving the hardenability of gear steel bars according to claim 1, characterized in that: The casting process parameters are: constant temperature and constant pulling speed during continuous casting, the pulling speed is 0.95-1.15 m / min, the secondary cooling water volume is 0.33-0.35 L / kg, and the electromagnetic stirring current at the end of solidification is 100-200A.
3. The method for improving the hardenability of gear steel bars according to claim 1, characterized in that: The maximum single pressing amount satisfies the following formula: Among them, ε is the maximum critical strain, v is the working pulling speed, h is the thickness of the ingot, r is the diameter of the reduction roll, b is the roll spacing, and a is the maximum single reduction.
4. The method for improving the hardenability of gear steel bars according to claim 3, characterized in that: When the solid fraction at the center of the reduction zone is between 0.05 and 1.0, the total reduction is calculated as follows: in, is the reduction coefficient, which ranges from 0.8 to 1.1, A is the total amount of reduction, V R is the pressing rate, t is the time, h is the thickness of the billet, W is the width of the billet, T L is the liquidus temperature of the steel grade, T S is the solidus temperature of the steel grade.
5. The method for improving the hardenability of gear steel bars according to claim 4, characterized in that: The relationship between the reduction and the central solid phase ratio is: When 0.05≤f s ≤0.08, the pressing amount is 1mm; when 0.18≤f s ≤0.20, the pressing amount is 2mm; When 0.55≤f s ≤0.58, the pressing amount is 2mm; When 0.98≤f s ≤1, the pressing amount is 2mm.
6. The method for improving the hardenability of gear steel bars according to claim 1, characterized in that: The steel used for the bar is 20CrMnTiH steel.
7. The method for improving the hardenability of gear steel bars according to claim 5, characterized in that: The rolling process is as follows: the hot ingot is heated to a temperature of 1160-1200°C and kept warm for 150 minutes, the starting rolling temperature is 1060-1100°C, the final rolling temperature is 900-1000°C, and the ingot is rolled into a φ70mm bar, which is then cooled to obtain the bar.
8. The method for improving the hardenability of gear steel bars according to claim 7, characterized in that: The rolling is performed in 4 to 6 passes, with the cross-sectional compression ratio of the first rolling pass being not less than 50%, the cross-sectional compression ratio of the last rolling pass being 10% to 25%, and the cross-sectional compression ratio of each of the remaining rolling passes being 30% to 45%.
9. The method for improving the hardenability of gear steel bars according to claim 1, characterized in that: The continuous casting machine is a full-arc continuous casting machine with six machines and six streams, and a casting section of 200mm×240mm.
10. A gear steel bar, characterized in that: The gear steel bar is prepared by the method described in any one of claims 1-9.
Citation Information
Patent Citations
Control method for casting of continuous-cast billet
CN101704079A
Gear steel 20CrMoSH and technology for improving hardenability stability thereof
CN109182905A
Method for relieving center segregation of super-thick plate blank high-carbon steel
CN112605358A
Pressure control method for improving macroscopic and semi-macroscopic segregation of high-carbon low-alloy steel
CN117226059A
Method for improving bar banded defect and mechanical property and cam shaft
CN117548638A
Cited By
Method for preparing hot-rolled middle rod for C-Mn series high-carbon wear-resistant steel ball based on continuous casting small square billet
CN122377868A
